Stalemate : why we can't win the war on terror and what we should do instead - Reeson, Greg C., 1968- (Government Institutes, 2011)
Since 9/11, the threat of terrorism has concerned Americans more than any other issue they face. Author Greg Reeson says this is not likely to change in the near future. In Stalemate, he argues that we are waging an unwinnable war against terrorism--that Muslim extremist ideology is a problem we can manage, but not soon solve. This conflict with terrorism will not end in victory or defeat, at least not in the traditional sense. The 9/11 attacks ushered in a new era in which the long-term aim of theUnited States will be the management and mitigation of Islamic extremist violence so that it inte.